Rules of engagement - Larsen, Ward; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2026)
"When a member of his Cabinet is killed in a plane President Jack Ryan suspects that the "accident" is anything but in this latest shocking entry in this #1 New York Times bestselling series. The White House is stunned when the secretary of commerce is killed on a trade mission to Turkey. President Jack Ryan isn't ready to write this off as a simple accident. The death represents not only the loss of a good friend, but the collapse of a vital operation to extract a key asset from the Middle East. As Lieutenant Commander Katie Ryan and her team work with the investigators to find the ause of the tragedy, one shocking revelation changes everything: There were supposed to be sixteen people on the plane, but there are only fifteen bodies. The quest for answers will lead the team deep into a quagmire of lies and deception. Piece by piece, they uncover a plan conceived by an enemy with no scruples -- a man convinced he has boxed in the United States with an operation as brilliant as it is brutal. Yet, like countless before him, this madman has overlooked the number one rule of international power: Never underestimate Jack Ryan."--